MICROBIAL ASSAY OF CYPROFLOXACIN IN A BONE IMPLANT (CHITOSAN –BOVINE HYDROXYAPATITE WITH CROSS-LINKER GLUTARALDEHYDE) TOWARDS Staphylococcus aureus ATCC 25923 - Esti Hendradi; Dewi Melani Hariyadi; Muhammad Faris Adrianto (UNEJ e-Proceeding)
Bone is one part of the body has an important roleto support the body's physiological functions (Porteret al., 2009). Complications of bone diseases andbone disorders caused by traumatic accidents mayresult in a gap (defect) on the bone. The healingprocess of damage or fracture is determined by thelevel of trauma and soft tissue damage (Strobel etal., 2011). Some cases of damage or injury to thebone can not undergo natural recovery (Porter et al.,2009). Therefore, clinical rehabilitation to overcomethe defect on the bone is expected to increase in linewith population growth (Mourino et al., 2010).Treatment rehabilitation of bone cannot beseparated from the risk of infection complications.Complications of bacterial infections can be treatedwith antibiotics. However, in the case of a crack(defect) occurs devascularity of bone tissue so thatthe delivery of antibiotics to the target tissue to beblocked. This resulted in the concentration of theantibiotic to the target so low that it cannotpenetrate the bacteria. The condition can lead tobacterial resistance to antibiotics (Li et al., 2010). Ahigh dose of antibiotics in the long term experiencedproblems because it can cause systemic toxicity andside effects (Mourino et al., 2010). To overcomethese problems, antibiotics can be done locally usinga certain drug delivery systems. The purpose of suchdelivery systems is to provide drug concentration ina specific location and ensure the drug releaseprofile for a certain time period (Dubnika et al.,2012). Drug delivery locally has several advantages,among others, (a) the systemic effects can beavoided, (b) the amount of drugs used less andsecure, and (c) the efficacy and efficiency of drugdelivery locally can be achieved (Harmankaya et al.,2013). Administration of antibiotics locally also tominimize side effects and risk of toxicity comparedto administration of systemic antibiotics. In addition,antibiotics locally also allows conduction in targettissues with high concentration (Mourino et al.,2010). The release of antibiotics on the targetnetwork is expected to last continuously for a certaintime and achieve a greater concentration than theminimum inhibitory concentration (MIC). Drugdelivery systems in a controlled manner (controlledrelease system) can help increase the bioavailabilityof antibiotics in target tissues. The system isdesigned to release the drug at the expectedlocation at a rate appropriate for a certain timeperiod (Mourino et al., 2010). In a previous studyshowed that a good composite is Ciprofloxacin: BHA:Chitosan = 10:30:60. Cross linker withglutaraldehyde (GA) 0.7% and with 10% activeingredient Ciprofloxacin can release Cyprofloxacinfor 30 days (Hendradi et al, 2015). This research willbe seen potency against Staphilococcus aureusATCC25923 Ciprofloxacin for 30 days.